Polarizing membrane manufacturing method and polarizing film manufacturing method

During the polarized film manufacturing process, when the water content of polyacetaldehyde film reaches 20% or above, liquid is used to penetrate the components into the membrane and fix these components in the drying step, the problem of increasing waste treatment of components in the prior art is solved, and more efficient membrane performance and durability are achieved.

JP2025069208AInactive Publication Date: 2025-04-30NITTO DENKO CORP
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2025008183
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-20
Filing Date
2025-01-21
Publication Date
2025-04-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When manufacturing polarized films, components added to the treatment bath increase the need for waste treatment and it is difficult to effectively include any components to improve the performance of the membrane.

Method used

During the polarized film manufacturing process, when the water content of the polyacetaldehyde film reaches 20% or more, a liquid is applied to penetrate the components in the liquid into the membrane and fix these components in the subsequent drying step, thereby improving the performance of the membrane.

Benefits of technology

This method enables polarized films to more easily contain various components, improving the performance and durability of the film while reducing the need for waste disposal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069208000001
    Figure 2025069208000001
  • Figure 2025069208000002
    Figure 2025069208000002
  • Figure 2025069208000003
    Figure 2025069208000003
Patent Text Reader

Abstract

To provide a polarizing membrane manufacturing method which can easily and sufficiently contain an optional component in the polarizing membrane.SOLUTION: A polarizing membrane manufacturing method includes: a step (I-1) for subjecting a polyvinyl alcohol film to at least a dyeing step, a crosslinking step, and a stretching step while conveying the polyvinyl alcohol film in a longitudinal direction to manufacture a polarizing membrane containing water; a step (I-2) for subjecting the polarizing membrane containing the obtained water to a step of applying a liquid in a state that a moisture content of the polarizing membrane is 20 wt.% or more to manufacture the polarizing membrane impregnated with a component in the liquid; and a step (I-3) for subjecting the polarizing membrane impregnated with the component in the obtained liquid to a drying step to manufacture the polarizing membrane after drying.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polarizing membrane and a method for producing a polarizing film. [Background technology]

[0002] Conventionally, a dyed polyvinyl alcohol film (containing a dichroic substance such as iodine or a dichroic dye) has been used as a polarizing film (polarizer) for use in various image display devices such as liquid crystal display devices and organic EL display devices, because it has both high transmittance and high polarization degree. The polarizing film is produced by subjecting a polyvinyl alcohol film to various treatments such as dyeing, crosslinking, stretching, etc. in a bath (treatment bath), and then drying the film. The polarizing film is usually used as a polarizing film (polarizing plate) in which a protective film such as triacetyl cellulose is attached to one or both sides of the polarizing film using an adhesive.

[0003] As a method for producing a polarizing film, for example, Patent Documents 1 and 2 disclose a method for improving the durability of a polarizing film by adding a component such as a metal salt containing zinc, copper, aluminum, etc. to a treatment bath to cause the polarizing film to contain the component. Patent Documents 3 and 4 disclose a method for producing a polarizing film by adding a component such as an organic titanium compound to a treatment bath. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 117659 [Patent Document 2] JP 2006-047978 A [Patent Document 3] JP 2008-46257 A [Patent Document 4] Japanese Patent Application Publication No. 6-172554 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the production method of a polarizing film, when the above-mentioned components are added to the treatment bath, problems arise such as the need to use a huge amount of the components and the need to treat the waste liquid of the treatment solution.

[0006] In view of the above circumstances, an object of the present invention is to provide a method for producing a polarizing film, which allows any component to be easily and sufficiently contained in the polarizing film.

[0007] Another object of the present invention is to provide a method for producing a polarizing film using the polarizing film obtained by the above-mentioned method for producing a polarizing film. [Means for solving the problem]

[0008] That is, the present invention relates to a method for producing a polarizing film, the method including: a step (I-1) of producing a water-containing polarizing film by subjecting a polyvinyl alcohol-based film to at least a dyeing step, a crosslinking step, and a stretching step while transporting the polyvinyl alcohol-based film in the longitudinal direction; a step (I-2) of applying a liquid to the obtained water-containing polarizing film while the polarizing film has a moisture content of 20% by weight or more to produce a polarizing film impregnated with a component in the liquid; and a step (I-3) of drying the obtained polarizing film impregnated with the component in the liquid to produce a dried polarizing film.

[0009] The present invention also relates to a method for producing a polarizing film, the method including: a step (II-0) of preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long-sized thermoplastic resin substrate; a step (II-1) of subjecting the obtained laminate to at least an auxiliary air-stretching treatment step, a dyeing treatment step, and an underwater stretching treatment step while transporting the obtained laminate in the longitudinal direction, to produce a laminate having a water-containing polarizing film; a step (II-2) of subjecting the obtained laminate having a water-containing polarizing film to a step of applying a liquid while the polarizing film has a moisture content of 20% by weight or more, to produce a laminate having a polarizing film impregnated with a component in the liquid; and a step (II-3) of subjecting the obtained laminate having a polarizing film impregnated with a component in the liquid to a drying treatment step, to produce a dried polarizing film.

[0010] The present invention also relates to a method for producing a polarizing film, comprising a step of laminating a transparent protective film via an adhesive layer to at least one surface of the polarizing film obtained by the method for producing a polarizing film. Effect of the Invention

[0011] Although the details of the mechanism of action of the method for producing a polarizing film of the present invention are unclear, it is presumed as follows: However, the present invention is not necessarily limited to this mechanism of action.

[0012] The method for producing a polarizing film of the present invention includes the steps of: (I-1) producing a water-containing polarizing film by subjecting a polyvinyl alcohol-based film to at least a dyeing step, a crosslinking step, and a stretching step while transporting the polyvinyl alcohol-based film in the longitudinal direction; (I-2) producing a polarizing film impregnated with a component in the liquid by subjecting the obtained water-containing polarizing film to a step of applying a liquid while the polarizing film has a moisture content of 20% by weight or more; and (I-3) producing a dried polarizing film by subjecting the obtained polarizing film impregnated with the component in the liquid. Alternatively, the method for producing a polarizing film of the present invention includes the steps of: forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long thermoplastic resin substrate to prepare a laminate (II-0); carrying out at least an auxiliary air-stretching step, a dyeing step, and an underwater stretching step on the obtained laminate while conveying the laminate in the longitudinal direction to produce a laminate having a polarizing film containing water (II-1); applying a liquid to the obtained laminate having a polarizing film containing water while the moisture content of the polarizing film is 20% by weight or more to produce a laminate having a polarizing film impregnated with a component in the liquid (II-2); and drying the obtained laminate having a polarizing film impregnated with a component in the liquid to produce a polarizing film after drying (II-3). In the conventional method for producing a polarizing film, a polyvinyl alcohol-based film is subjected to at least a dyeing step, a crosslinking step, and a stretching step, and then a drying step is subsequently performed. Alternatively, in the conventional method for producing a polarizing film, a step of preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long-sized thermoplastic resin substrate, and a step of subjecting the obtained laminate to at least an auxiliary air-stretching step, a dyeing step, and an underwater stretching step, followed by a drying step, are performed. On the other hand, in the method for producing a polarizing film of the present invention, as described above, a polarizing film containing water or a laminate having a polarizing film containing water is produced. The polarizing film containing water or the polarizing film in the laminate having a polarizing film containing water is subjected to a step of applying a liquid while the moisture content of the polarizing film is 20% by weight or more, so that any component contained in the liquid can be easily and sufficiently impregnated into the polarizing film containing water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Method of manufacturing polarizing film> The method for producing a polarizing film of the present invention includes the steps of: (I-1) producing a water-containing polarizing film by subjecting a polyvinyl alcohol-based film to at least a dyeing step, a crosslinking step, and a stretching step while transporting the polyvinyl alcohol-based film in the longitudinal direction; (I-2) producing a polarizing film impregnated with a component in the liquid by subjecting the obtained water-containing polarizing film to a step of applying a liquid while the polarizing film has a moisture content of 20% by weight or more; and (I-3) producing a dried polarizing film by subjecting the obtained polarizing film impregnated with the component in the liquid.

[0014] <Step (I-1) of Producing a Water-Containing Polarizing Film> The method for producing a polarizing film of the present invention includes a step (I-1) of producing a polarizing film containing water by subjecting a polyvinyl alcohol-based film to at least a dyeing step, a crosslinking step, and a stretching step while transporting the polyvinyl alcohol-based film in a longitudinal direction.

[0015] The polyvinyl alcohol (PVA) film can be used without any particular limitation as long as it has transparency in the visible light region and disperses and adsorbs dichroic substances such as iodine and dichroic dyes. In addition, the PVA film usually used as a raw sheet preferably has a thickness of about 1 to 100 μm, more preferably about 1 to 50 μm, and preferably has a width of about 100 to 5000 mm.

[0016] The material of the polyvinyl alcohol-based film includes polyvinyl alcohol or its derivatives. Examples of the derivatives of polyvinyl alcohol include polyvinyl formal, polyvinyl acetal, olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and those modified with alkyl esters and acrylamides. The polyvinyl alcohol preferably has an average degree of polymerization of about 100 to 10,000, more preferably about 1,000 to 10,000, and even more preferably about 1,500 to 4,500. The polyvinyl alcohol preferably has a saponification degree of about 80 to 100 mol%, and more preferably about 95 mol% to 99.95 mol. The average degree of polymerization and the saponification degree can be determined in accordance with JIS K 6726.

[0017] The polyvinyl alcohol-based film may contain additives such as plasticizers and surfactants. Examples of the plasticizers include polyols such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol, and condensates thereof. The amount of the additives used is not particularly limited, but is preferably about 20% by weight or less in the polyvinyl alcohol-based film.

[0018] <Dyeing process> The dyeing step is a treatment step of immersing a polyvinyl alcohol-based film in a dye bath, and allows iodine or a dichroic substance such as a dichroic dye to be adsorbed and oriented on the polyvinyl alcohol-based film. The dyeing solution is usually preferably an aqueous iodine solution, and contains iodine and an iodide as a dissolution aid. Examples of the iodide include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is preferred.

[0019] The concentration of iodine in the dye bath is preferably about 0.01 to 1% by weight, more preferably about 0.02 to 0.5% by weight, and the concentration of iodide in the dye bath is preferably about 0.01 to 10% by weight, more preferably about 0.05 to 5% by weight.

[0020] The temperature of the dye bath is preferably about 10 to 50° C., and more preferably about 15 to 45° C. The immersion time in the dye bath cannot be determined in general because the degree of dyeing of the polyvinyl alcohol film is affected by the temperature of the dye bath, but is preferably about 10 to 300 seconds, and more preferably about 20 to 240 seconds. The dyeing step may be carried out only once, or may be carried out multiple times as necessary.

[0021] <Crosslinking process> The crosslinking step is a treatment step in which the polyvinyl alcohol-based film dyed in the dyeing step is immersed in a treatment bath (crosslinking bath) containing a boron compound, and the polyvinyl alcohol-based film is crosslinked by the boron compound, so that iodine molecules or dye molecules can be adsorbed to the crosslinked structure. Examples of the boron compound include boric acid, borate salts, and borax. The crosslinking bath is generally an aqueous solution, but may also be, for example, a mixed solution of water and an organic solvent miscible with water. The crosslinking bath may also contain an iodide such as potassium iodide.

[0022] The concentration of the boron compound in the crosslinking bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight. When an iodide such as potassium iodide is used in the crosslinking bath, the concentration of the iodide such as potassium iodide in the crosslinking bath is preferably about 1 to 15% by weight, and even more preferably about 1.5 to 10% by weight.

[0023] The temperature of the crosslinking bath is preferably about 20 to 70° C., and more preferably about 30 to 60° C. The immersion time in the crosslinking bath cannot be determined in general because the degree of crosslinking of the polyvinyl alcohol film is affected by the temperature of the crosslinking bath, but is preferably about 5 to 300 seconds, and more preferably about 10 to 200 seconds. The crosslinking step may be carried out only once, or may be carried out multiple times as necessary.

[0024] <Stretching process> The stretching step is a process step of stretching a polyvinyl alcohol-based film at least in one direction to a predetermined magnification. In general, the polyvinyl alcohol-based film is uniaxially stretched in the conveying direction (longitudinal direction). The stretching method is not particularly limited, and either a wet stretching method or a dry stretching method can be used. The stretching step may be carried out only once, or may be carried out multiple times as necessary. The stretching step may be carried out at any stage in the production of a polarizing film.

[0025] The treatment bath (stretching bath) in the wet stretching method can generally use a solvent such as water or a mixed solution of water and an organic solvent miscible with water. The stretching bath can contain an iodide such as potassium iodide. When an iodide such as potassium iodide is used in the stretching bath, the concentration of the iodide such as potassium iodide in the stretching bath is preferably about 1 to 15% by weight, more preferably about 2 to 10% by weight. The treatment bath (stretching bath) can also contain the boron compound in order to improve the degree of crosslinking. In this case, the concentration of the boron compound in the stretching bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight.

[0026] The temperature of the stretching bath is preferably about 25 to 80° C., more preferably about 40 to 75° C. The immersion time in the stretching bath cannot be determined in general because the degree of stretching of the polyvinyl alcohol film is affected by the temperature of the stretching bath, but is preferably about 10 to 800 seconds, more preferably about 30 to 500 seconds. The stretching treatment in the wet stretching method may be performed together with one or more of the dyeing step, the crosslinking step, the swelling step described later, and the washing step described later.

[0027] Examples of the dry stretching method include a roll-to-roll stretching method, a heated roll stretching method, a compression stretching method, etc. The dry stretching method may be carried out together with a drying step described later.

[0028] The total stretching ratio (cumulative stretching ratio) applied to the polyvinyl alcohol film can be appropriately set depending on the purpose, but is preferably about 2 to 7 times, more preferably about 3 to 6.8 times, and even more preferably about 3.5 to 6.5 times.

[0029] In the step of producing the water-containing polarizing film, the polyvinyl alcohol-based film is subjected to the dyeing step, the crosslinking step, and the stretching step, and may also be subjected to a swelling step and a washing step.

[0030] <Swelling process> The swelling step is a treatment step of immersing the polyvinyl alcohol-based film in a swelling bath, which can remove dirt and blocking agents on the surface of the polyvinyl alcohol-based film, and can suppress uneven dyeing by swelling the polyvinyl alcohol-based film. The swelling bath usually uses a medium mainly composed of water, such as distilled water or pure water. The swelling bath may contain surfactants, alcohol, etc., as appropriate, according to a conventional method.

[0031] The temperature of the swelling bath is preferably about 10 to 60° C., and more preferably about 15 to 45° C. The immersion time in the swelling bath cannot be determined in general because the degree of swelling of the polyvinyl alcohol film is affected by the temperature of the swelling bath, but is preferably about 5 to 300 seconds, and more preferably about 10 to 200 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.

[0032] <Cleaning process> The washing step is a treatment step of immersing the polyvinyl alcohol-based film in a washing bath, and can remove foreign matter remaining on the surface of the polyvinyl alcohol-based film. The washing bath generally uses a medium mainly composed of water, such as water, distilled water, or pure water. An iodide such as potassium iodide can be used in the washing bath. In this case, the concentration of the iodide such as potassium iodide in the washing bath is preferably about 1 to 10% by weight, more preferably about 2 to 4% by weight, and even more preferably about 1.6 to 3.8% by weight.

[0033] The temperature of the cleaning bath is preferably about 5 to 50° C., more preferably about 10 to 40° C., and even more preferably about 15 to 30° C. The immersion time in the cleaning bath cannot be determined in general because the degree of cleaning of the polyvinyl alcohol film is affected by the temperature of the cleaning bath, but is preferably about 1 to 100 seconds, more preferably about 2 to 50 seconds, and even more preferably about 3 to 20 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.

[0034] Furthermore, each treatment bath in the swelling step, the dyeing step, the crosslinking step, the stretching step and the washing step may contain additives such as zinc salts, pH adjusters, pH buffers and other salts. Examples of the zinc salts include zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of the pH adjusters include strong acids such as hydrochloric acid, sulfuric acid and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of the pH buffers include carboxylic acids such as acetic acid, oxalic acid and citric acid and their salts, inorganic weak acids such as phosphoric acid and carbonic acid and their salts. Examples of the other salts include chlorides such as sodium chloride, potassium chloride and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0035] <Process (I-2) for producing a polarizing film impregnated with liquid components> The method for producing a polarizing film of the present invention includes a step (I-2) of applying a liquid to the water-containing polarizing film obtained above while the polarizing film has a moisture content of 20% by weight or more to produce a polarizing film impregnated with a component in the liquid. The component in the liquid is usually a solute contained in a solution. The solute may be any substance that can be dissolved or dispersed in a solvent, and the single compound may be any of a gaseous substance, a liquid substance, and a solid substance. When the solute is a liquid substance (for example, under conditions of 25° C. and 1 atm), the liquid substance itself (the liquid substance itself) may be a liquid or a component in the liquid.

[0036] In the step (I-2), from the viewpoint of facilitating impregnation of the components contained in the liquid and making it easier for the components to penetrate into the polarizing film in the thickness direction, the moisture content of the polarizing film is preferably 22% by weight or more, and more preferably 25% by weight or more. From the viewpoint of preventing wrinkles during transportation, the moisture content of the polarizing film is preferably 70% by weight or less, and more preferably 60% by weight or less.

[0037] The coating method in the step of applying the liquid may be a conventional coating method, such as roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. The coating surface of the polarizing film may be one side or both sides.

[0038] The component in the liquid may be a water-soluble compound from the viewpoint of facilitating impregnation of the component into the water-containing polarizing film. The water-soluble compound is one having a solubility of 1 g or more in 100 g of water at 25° C.

[0039] Examples of components in the liquid include zinc salts (zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate; etc.); organic titanium compounds (titanium alkoxides, titanium chelates, titanium chelate ammonium salts, titanium chelate acylates, etc.), organic zirconium compounds (zirconyl alkoxides, zirconyl chelates, zirconyl chelate ammonium salts, zirconyl acylates), alkali metal salts, alkaline earth metal salts, metal halides, etc.

[0040] In addition, the components in the liquid include a compound having a radical scavenging function (also called a radical scavenger). The compound having a radical scavenging function can capture radicals generated by the polyvinyl alcohol of the polarizing film when heated, and suppress polyenization, thereby improving the heat durability of the polarizing film. From the viewpoint of easily suppressing polyenization, the compound having a radical scavenging function is preferably, for example, a compound having a nitroxy radical or a nitroxide group.

[0041] Examples of the compound having a nitroxy radical or a nitroxide group include compounds having an organic group having the following structure: [ka] (In general formula (1), R 1 represents an oxy radical, and R 2 From R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n represents 0 or 1.) In addition, in general formula (1), the left of the dotted line represents any organic group.

[0042] Examples of the compound having the above organic group include compounds represented by the following general formulas (2) to (5). [ka] (In general formula (2), R 1 ~R 5 , and n are the same as above, and R 6 represents a hydrogen atom, or an alkyl group, acyl group, or aryl group having 1 to 10 carbon atoms. [ka] (In general formula (3), R 1 From R 5 , and n are the same as above, and R 7 and R 8 each independently represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms. [ka] (In general formula (4), R 1 From R 5 , and n are the same as above, and R 9 From R 11 each independently represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an acyl group, an amino group, an alkoxy group, a hydroxyl group, or an aryl group. [ka] (In general formula (5), R 1 From R 5 , and n are the same as above, and R 12represents a hydrogen atom, or an alkyl group having 1 to 10 carbon atoms, an amino group, an alkoxy group, a hydroxyl group, or an aryl group.

[0043] In the general formulas (1) to (5), R 2 From R 5 From the viewpoint of availability, R is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. 6 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 7 and R 8 are preferably independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. 9 From R 11 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. 12 is preferably a hydroxy group, an amino group, or an alkoxy group. In the general formulas (1) to (5), n is preferably 1 from the viewpoint of availability.

[0044] Examples of the compound having a nitroxy radical or a nitroxide group include the following compounds: [ka] (In the general formula (6), R represents a hydrogen atom, or an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms.) [ka] [ka]

[0045] In addition, the components in the liquid include a compound having a crosslinking function (also referred to as a crosslinking agent). The compound having a crosslinking function reacts with the hydroxyl group of the polyvinyl alcohol of the polarizing film to form a crosslinked structure, and can improve the durability of the polarizing film against humidification. From the viewpoint of improving the durability against humidification, examples of the compound having a crosslinking function include organic compounds having an isocyanate group, an isocyanate-derived functional group, an epoxy group, a carbonyl group, an aziridine ring, a vinyl ether group, a vinyl sulfone group, and an oxazoline group, as well as organic titanium compounds (titanium alkoxide, titanium chelate, titanium chelate ammonium salt, titanium chelate acylate, etc.).

[0046] In addition, the components in the liquid include compounds (also called plasticizers) that have the function of imparting plasticity. The compounds that have the function of imparting plasticity impart plasticity to the polarizing film, thereby reducing quality defects such as dents caused by the pressing force. Examples of the compounds that have the function of imparting plasticity include ethylene glycol, polyethylene glycol, other ethylene glycol derivatives, and glycerin.

[0047] In addition, the components in the liquid include dye-based compounds (also called dyes). The dye-based compounds can impart properties such as hue adjustment and pattern printing to the polarizing film. Examples of the dye-based compounds include azo compounds, anthraquinone compounds, and quinophthalone compounds.

[0048] The liquid cannot be determined in general because it is affected by the application (coating) method described above. However, from the viewpoint of efficiently penetrating the components in the liquid, the concentration of the components in the liquid is preferably 0.1% by weight or more, and more preferably 1.0% by weight or more, and from the viewpoint of preventing quality defects due to precipitation of the components in the liquid, the concentration is preferably 30% by weight or less, and more preferably 20% by weight or less.

[0049] Examples of the solvent include water; water-soluble solvents such as methanol, ethanol, ethylene glycol, polyethylene glycol, other ethylene glycol derivatives, glycerin, and dimethyl sulfoxide.

[0050] The time from the end of the step (I-1) to the start of the step (I-2) (the transport time of the polarizing film in actual production) is, from the viewpoint of retaining the moisture contained in the water-containing polarizing film or from the viewpoint of productivity, preferably at a temperature of about 15°C to 35°C, and more preferably at a temperature of about 20°C to 30°C, and 300 seconds or less, more preferably 180 seconds or less, even more preferably 60 seconds or less, and even more preferably 10 seconds or less.

[0051] In the step (I-2), if necessary, a step of applying a liquid to the water-containing polarizing film may be carried out, followed by a step of impregnating the film with a part of the liquid and removing the remaining liquid. Examples of a method for removing the liquid include a wiping method using a rag or a sponge roll, a suction removal method, a removal method using air blowing, and a scraping removal method using a bar or a gravure roll.

[0052] <Process for Producing Dried Polarizing Film (I-3)> The method for producing a polarizing film of the present invention includes a step (I-3) of subjecting the polarizing film impregnated with the components in the liquid obtained above to a drying step to produce a dried polarizing film.

[0053] The drying step is a step of drying the polarizing film impregnated with the components in the liquid obtained above to obtain a polarizing film, and a polarizing film having a desired moisture content can be obtained by drying. The drying can be performed by any appropriate method, for example, natural drying, air drying, or heat drying.

[0054] The drying temperature is preferably about 20 to 150° C., and more preferably about 25 to 100° C. The drying time cannot be determined in general because the degree of drying of the polarizing film is affected by the drying temperature, but is preferably about 10 to 600 seconds, and more preferably about 30 to 300 seconds. The drying step may be carried out only once, or may be carried out multiple times as necessary.

[0055] The dried polarizing film preferably has a moisture content of 10% by weight or more, more preferably 12% by weight or more, from the viewpoint of preventing quality defects such as dents due to loss of plasticity, and preferably has a moisture content of 20% by weight or less, more preferably 16% by weight or less, from the viewpoint of improving optical properties such as the degree of polarization. In the case of a dried polarizing film having a thickness of about 8 μm or less, which will be described later, the dried polarizing film preferably has a moisture content of 2% by weight or more, more preferably 3% by weight or more, from the viewpoint of preventing quality defects such as dents due to loss of plasticity, and preferably has a moisture content of 20% by weight or less, more preferably 10% by weight or less, from the viewpoint of improving optical properties such as the degree of polarization.

[0056] The dried polarizing film has a thickness of preferably about 1 to 30 μm, more preferably about 5 to 25 μm, and further preferably 5 to 20 μm. In particular, in order to obtain a dried polarizing film having a thickness of about 8 μm or less, the following method for producing a thin polarizing film can be applied, in which a laminate including a polyvinyl alcohol-based resin layer formed on a thermoplastic resin substrate is used as the polyvinyl alcohol-based film.

[0057] <Manufacturing method of polarizing film (thin polarizing film)> The method for producing a polarizing film (thin polarizing film) includes the steps of: preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long-sized thermoplastic resin substrate (II-0); producing a laminate having a water-containing polarizing film by subjecting the obtained laminate to at least an auxiliary air-stretching treatment step, a dyeing treatment step, and an underwater stretching treatment step while transporting the obtained laminate in the longitudinal direction; producing a laminate having a water-containing polarizing film by subjecting the obtained laminate having a water-containing polarizing film to a step of applying a liquid while the moisture content of the polarizing film is 20% by weight or more, thereby producing a laminate having a polarizing film impregnated with a component in the liquid (II-2); and producing a laminate having a polarizing film impregnated with a component in the liquid by subjecting the obtained laminate having a polarizing film impregnated with a component in the liquid to a drying treatment step to produce a dried polarizing film (II-3).

[0058] <Step of preparing laminate (II-0)> The method for producing a polarizing film (thin polarizing film) of the present invention includes a step (II-0) of forming a polyvinyl alcohol-based resin layer (PVA-based resin layer) containing a polyvinyl alcohol-based resin (PVA-based resin) on one side of a long thermoplastic resin substrate to prepare a laminate.

[0059] The laminate may be prepared by any suitable method, for example, by applying a coating liquid containing the PVA resin to the surface of the thermoplastic resin substrate and drying the coating liquid. The thickness of the thermoplastic resin substrate is preferably about 20 to 300 μm, more preferably about 50 to 200 μm. The thickness of the PVA resin layer is preferably about 3 to 40 μm, more preferably about 3 to 20 μm.

[0060] The thermoplastic resin substrate preferably has a water absorption rate of about 0.2% or more, more preferably about 0.3% or more, from the viewpoint of absorbing water to greatly reduce the stretching stress and being able to be stretched at a high ratio. On the other hand, the thermoplastic resin substrate preferably has a water absorption rate of about 3% or less, more preferably about 1% or less, from the viewpoint of preventing defects such as a significant decrease in the dimensional stability of the thermoplastic resin substrate and a deterioration in the appearance of the resulting polarizing film. The water absorption rate can be adjusted, for example, by introducing a modifying group into the constituent material of the thermoplastic resin substrate. The water absorption rate is a value determined in accordance with JIS K 7209.

[0061] The thermoplastic resin substrate preferably has a glass transition temperature (Tg) of about 120° C. or less from the viewpoint of ensuring sufficient stretchability of the laminate while suppressing crystallization of the PVA-based resin layer. Furthermore, in consideration of the plasticization of the thermoplastic resin substrate by water and the underwater stretching being performed well, the glass transition temperature (Tg) is more preferably about 100° C. or less, and even more preferably about 90° C. or less. On the other hand, the glass transition temperature of the thermoplastic resin substrate is preferably about 60° C. or more from the viewpoint of preventing defects such as deformation of the thermoplastic resin substrate when applying and drying a coating liquid and producing a good laminate. The glass transition temperature can be adjusted, for example, by introducing a modifying group into the constituent material of the thermoplastic resin substrate or by heating using a crystallizing material. The glass transition temperature (Tg) is a value determined in accordance with JIS K 7121.

[0062] Any suitable thermoplastic resin may be used as the constituent material of the thermoplastic resin substrate. Examples of the thermoplastic resin include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferred, and amorphous polyethylene terephthalate resins are preferably used because the thermoplastic resin substrate has excellent stretchability and can suppress crystallization during stretching. Examples of amorphous polyethylene terephthalate resins include copolymers containing isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acids, and copolymers containing cyclohexanedimethanol or diethylene glycol as glycols.

[0063] The thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.) before forming the PVA-based resin layer, or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved. In addition, the thermoplastic resin substrate may be stretched before forming the PVA-based resin layer.

[0064] The coating liquid is a solution in which a PVA-based resin is dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine, with water being preferred. These can be used alone or in combination of two or more. The concentration of the PVA-based resin in the coating liquid is preferably about 3 to 20 parts by weight relative to 100 parts by weight of the solvent, from the viewpoint of forming a uniform coating film that is in close contact with the thermoplastic resin substrate.

[0065] The coating liquid preferably contains a halide from the viewpoint of improving the orientation of polyvinyl alcohol molecules by stretching. Any appropriate halide can be used as the halide, and examples thereof include iodide and sodium chloride. Examples of the iodide include potassium iodide, sodium iodide, and lithium iodide, and potassium iodide is preferred. The concentration of the halide in the coating liquid is preferably about 5 to 20 parts by weight, and more preferably about 10 to 15 parts by weight, based on 100 parts by weight of the PVA resin.

[0066] The coating liquid may contain additives, such as plasticizers, such as ethylene glycol and glycerin, and surfactants, such as nonionic surfactants.

[0067] The coating method of the coating liquid may be any appropriate method, such as roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. The drying temperature of the coating liquid is preferably about 50° C. or higher.

[0068] <Step (II-1) of Producing a Laminate Having a Water-Containing Polarizing Film> The method for producing a polarizing film (thin polarizing film) of the present invention includes a step (II-1) of producing a laminate having a water-containing polarizing film by subjecting the laminate obtained above to at least an auxiliary in-air stretching treatment step, a dyeing treatment step, and an underwater stretching treatment step while transporting the laminate in the longitudinal direction.

[0069] In the auxiliary air-stretching process, the laminate can be stretched at a high ratio since the crystallization of the thermoplastic resin substrate can be suppressed. The stretching method in the auxiliary air-stretching process may be fixed-end stretching (e.g., a method of stretching using a tenter stretching machine) or free-end stretching (e.g., a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds), but free-end stretching is preferred from the viewpoint of obtaining high optical properties.

[0070] The stretching ratio in the auxiliary in-air stretching step is preferably about 2 to 3.5. The auxiliary in-air stretching step may be performed in one stage or in multiple stages. When performed in multiple stages, the stretching ratio is the product of the stretching ratios in each stage.

[0071] The stretching temperature in the auxiliary air-stretching process can be set to any appropriate value depending on the material forming the thermoplastic resin substrate, the stretching method, etc., and is, for example, preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) + 10° C., and even more preferably equal to or higher than the glass transition temperature (Tg) + 15° C. On the other hand, the upper limit of the stretching temperature is preferably about 170° C., from the viewpoint of suppressing rapid crystallization of the PVA-based resin and suppressing defects due to crystallization (for example, preventing the orientation of the PVA-based resin layer due to stretching).

[0072] If necessary, an insolubilization treatment step may be performed after the auxiliary air-stretching treatment step and before the dyeing treatment step or the underwater stretching treatment step. The insolubilization treatment step is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. By performing the insolubilization treatment step, water resistance is imparted to the PVA-based resin layer, and it is possible to prevent a decrease in the orientation of PVA when immersed in water. The concentration of the aqueous solution of boric acid is preferably about 1 to 5 parts by weight relative to 100 parts by weight of water. The liquid temperature of the insolubilization bath is preferably about 20 to 50°C.

[0073] The dyeing process is carried out by dyeing the PVA-based resin layer with iodine. Examples of the adsorption method include a method of immersing the PVA-based resin layer (laminate) in a dyeing solution containing iodine, a method of applying the dyeing solution to the PVA-based resin layer, and a method of spraying the dyeing solution onto the PVA-based resin layer, and the like. The method of immersing the PVA-based resin layer (laminate) in a dyeing solution containing iodine is preferred.

[0074] The amount of iodine in the dye bath is preferably about 0.05 to 0.5 parts by weight relative to 100 parts by weight of water. In order to increase the solubility of iodine in water, it is preferable to mix the iodide in the iodine aqueous solution. The amount of iodide is preferably about 0.1 to 10 parts by weight, more preferably about 0.3 to 5 parts by weight, relative to 100 parts by weight of water. The liquid temperature of the dye bath is preferably about 20 to 50°C in order to suppress dissolution of the PVA resin. In addition, the immersion time is preferably about 5 seconds to 5 minutes, more preferably about 30 seconds to 90 seconds, from the viewpoint of ensuring the transmittance of the PVA resin layer. In order to obtain a polarizing film having good optical properties, the ratio of the contents of iodine and iodide in the iodine aqueous solution is preferably about 1:5 to 1:20, more preferably about 1:5 to 1:10.

[0075] If necessary, a crosslinking process may be performed after the dyeing process and before the underwater stretching process. The crosslinking process is typically performed by immersing the PVA resin layer in an aqueous boric acid solution. The crosslinking process imparts water resistance to the PVA resin layer, and prevents the orientation of the PVA from decreasing when the layer is immersed in high-temperature water in the subsequent underwater stretching process. The boric acid concentration of the aqueous boric acid solution is preferably about 1 to 5 parts by weight relative to 100 parts by weight of water. In addition, when the crosslinking process is performed, it is preferable to further add the iodide to the crosslinking bath. By adding the iodide, it is possible to suppress the elution of iodine adsorbed to the PVA resin layer. The amount of the iodide added is preferably about 1 to 5 parts by weight relative to 100 parts by weight of water. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably about 20 to 50°C.

[0076] The underwater stretching process is performed by immersing the laminate in a stretching bath. According to the underwater stretching process, stretching can be performed at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched at a high magnification while suppressing crystallization. The stretching method in the underwater stretching process may be fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls with different peripheral speeds), but free-end stretching is preferred from the viewpoint of obtaining high optical properties.

[0077] The underwater stretching step is preferably performed by immersing the laminate in an aqueous boric acid solution (stretching in an aqueous boric acid solution). By using an aqueous boric acid solution as the stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. The boric acid concentration of the aqueous boric acid solution is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, per 100 parts by weight of water. In addition, an iodide may be blended into the stretching bath (aqueous boric acid solution). The liquid temperature of the stretching bath is preferably about 40 to 85°C, more preferably about 60 to 75°C. The immersion time of the laminate in the stretching bath is preferably about 15 seconds to 5 minutes.

[0078] The stretching ratio in the underwater stretching process is preferably about 1.5 times or more, and more preferably about 3 times or more.

[0079] The total stretching ratio of the laminate is preferably about 5 times or more, and more preferably about 5.5 times or more, relative to the original length of the laminate.

[0080] After the underwater stretching step, a washing step is preferably carried out. The washing step is typically carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0081] Furthermore, each treatment bath in the dyeing process, the underwater stretching process, the insolubilization process, the crosslinking process, and the washing process may contain additives such as zinc salts, pH adjusters, pH buffers, and other salts. Examples of the zinc salts include zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of the pH adjusters include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of the pH buffers include carboxylic acids such as acetic acid, oxalic acid, and citric acid, and salts thereof, and inorganic weak acids such as phosphoric acid and carbonic acid, and salts thereof. Examples of the other salts include chlorides such as sodium chloride, potassium chloride, and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0082] <Step (II-2) of Producing a Laminate Having a Polarizing Film Impregnated with a Component in a Liquid> The method for producing a polarizing film (thin polarizing film) of the present invention includes a step (II-2) of producing a laminate having a polarizing film impregnated with a component in the liquid by applying a liquid to the laminate having the water-containing polarizing film obtained above while the moisture content of the polarizing film is at least 20% by weight. In the step (II-2), all of the above-mentioned step (I-2) for producing a polarizing film impregnated with a component in the liquid can be applied. However, the liquid is applied (coated) to the surface of the polarizing film.

[0083] In the step (II-2), from the viewpoint of facilitating impregnation of the components contained in the liquid and making it easier for the components to penetrate into the polarizing film in the thickness direction, the moisture content of the polarizing film is preferably 22% by weight or more, and more preferably 25% by weight or more. Additionally, from the viewpoint of preventing wrinkles during transportation, the moisture content of the polarizing film is preferably 70% by weight or less, and more preferably 60% by weight or less.

[0084] The time from the end of the step (II-1) to the start of the step (II-2) (the transport time of the laminate having the polarizing film in the actual production) is, from the viewpoint of retaining the moisture contained in the water-containing polarizing film or from the viewpoint of productivity, preferably at a temperature of about 15° C. to 35° C., and preferably at a temperature of about 20° C. to 30° C., and 300 seconds or less, more preferably 180 seconds or less, even more preferably 60 seconds or less, and even more preferably 10 seconds or less.

[0085] <Process for producing a dried polarizing film (II-3)> The method for producing a polarizing film (thin polarizing film) of the present invention includes a step (II-3) of subjecting the laminate having the polarizing film impregnated with the components in the liquid obtained above to a drying treatment step to produce a dried polarizing film.

[0086] The drying process is carried out by any appropriate method, and examples of the method include natural drying, air drying, and heat drying. The drying process may be carried out by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll). Drying using a heating roll efficiently suppresses heat curling of the laminate, making it possible to produce a polarizing film with excellent appearance, and since the laminate can be dried while being kept flat, it is possible to suppress not only curling but also wrinkles. In addition, from the viewpoint of improving the optical properties of the obtained polarizing film by shrinking the laminate in the width direction during the drying process, the shrinkage rate of the laminate in the width direction due to the drying process is preferably about 1 to 10%, more preferably about 2 to 8%.

[0087] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, contact time with the heating rolls, etc. The temperature of the heating rolls is preferably about 60 to 120°C, more preferably about 65 to 100°C, and even more preferably 70 to 80°C. From the viewpoint of satisfactorily increasing the crystallinity of the thermoplastic resin and satisfactorily suppressing curling, the number of transport rolls is usually about 2 to 40, preferably about 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably about 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0088] The heating roll may be installed in a heating furnace or in a normal production line (under room temperature environment). It is preferably installed in a heating furnace equipped with a blowing means. By using drying with the heating roll and hot air drying in combination, it is possible to suppress a steep temperature change between the heating rolls, and it is possible to easily control the shrinkage in the width direction. The hot air drying temperature is preferably about 30 to 100°C. In addition, the hot air drying time is preferably about 1 to 300 seconds.

[0089] <Method of manufacturing polarizing film> The method for producing a polarizing film of the present invention includes a step of laminating a transparent protective film via an adhesive layer to at least one surface of the polarizing film obtained by the method for producing a polarizing film described above.

[0090] The transparent protective film is not particularly limited, and various transparent protective films used in polarizing films can be used. As a material constituting the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. can be used. Examples of the thermoplastic resin include cellulose ester resins such as triacetyl cellulose, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins such as nylon and aromatic polyamide, polyimide resins, polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins) having a cyclo or norbornene structure, polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. In addition, the transparent protective film can be a cured layer formed from a thermosetting resin or an ultraviolet curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone resin. Among these, cellulose ester resins, polycarbonate resins, (meth)acrylic resins, cyclic polyolefin resins, and polyester resins are preferred.

[0091] The thickness of the transparent protective film can be determined as appropriate, but generally, from the viewpoints of workability such as strength and handleability, thinness, etc., it is preferably about 1 to 500 μm, more preferably about 1 to 300 μm, and even more preferably about 5 to 100 μm.

[0092] When the transparent protective films are attached to both sides of the polarizing film, the transparent protective films on both sides may be the same or different.

[0093] The transparent protective film may be a retardation plate having a front retardation of 40 nm or more and / or a thickness retardation of 80 nm or more. The front retardation is usually controlled to be in the range of 40 to 200 nm, and the thickness retardation is usually controlled to be in the range of 80 to 300 nm. When a retardation plate is used as the transparent protective film, the retardation plate also functions as the transparent protective film, so that the film can be made thinner.

[0094] Examples of the retardation plate include a birefringent film obtained by uniaxial or biaxial stretching of a polymeric material, an oriented film of a liquid crystal polymer, and an oriented layer of a liquid crystal polymer supported by a film. The thickness of the retardation plate is not particularly limited, but is generally about 20 to 150 μm. The retardation plate may be used by laminating it to a transparent protective film that does not have a retardation.

[0095] The transparent protective film may contain any suitable additives, such as an ultraviolet absorbing agent, an antioxidant, a lubricant, a plasticizer, a release agent, a coloring inhibitor, a flame retardant, an antistatic agent, a pigment, and a colorant.

[0096] The surface of the transparent protective film to which the polarizing film is not attached may be provided with a functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, an anti-glare layer, etc. The functional layer such as the hard coat layer, the anti-reflection layer, the anti-sticking layer, the diffusion layer, the anti-glare layer, etc. may be provided on the protective film itself, or may be provided separately from the protective film.

[0097] The polarizing film and the transparent protective film, or the polarizing film and the functional layer, are usually attached to each other via a pressure-sensitive adhesive layer or an adhesive layer.

[0098] As the adhesive forming the adhesive layer, various adhesives used in polarizing films can be used, and examples thereof include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinyl porolidone-based adhesives, polyacrylamide-based adhesives, cellulose-based adhesives, etc. Among these, acrylic-based adhesives are preferred.

[0099] Examples of the method for forming the adhesive layer include a method in which the adhesive is applied to a release-treated separator or the like, dried to form an adhesive layer, and then transferred to a polarizing film or the like, or a method in which the adhesive is applied to a polarizing film or the like, dried to form an adhesive layer, etc. The thickness of the adhesive layer is not particularly limited and is, for example, about 1 to 100 μm, and preferably about 2 to 50 μm.

[0100] The adhesive for forming the adhesive layer may be any of various adhesives used in polarizing films, including, for example, isocyanate-based adhesives, polyvinyl alcohol-based adhesives, gelatin-based adhesives, vinyl latex-based adhesives, water-based polyesters, etc. These adhesives are usually used as aqueous solutions, and contain 0.5 to 60% by weight of solids.

[0101] In addition to the above, examples of the adhesive include active energy ray curable adhesives such as ultraviolet ray curable adhesives and electron beam curable adhesives. Examples of the active energy ray curable adhesives include (meth)acrylate adhesives. Examples of the curable components in the (meth)acrylate adhesives include compounds having a (meth)acryloyl group and compounds having a vinyl group. In addition, compounds having an epoxy group or an oxetanyl group can also be used as cationic polymerization curable adhesives. The compound having an epoxy group is not particularly limited as long as it has at least two epoxy groups in the molecule, and various commonly known curable epoxy compounds can be used.

[0102] The adhesive may be applied to either the transparent protective film side (or the functional layer side) or the polarizing film side, or may be applied to both. After lamination, a drying step is performed to form an adhesive layer consisting of a coated and dried layer. After the drying step, ultraviolet rays or electron beams may be irradiated as necessary. The thickness of the adhesive layer is not particularly limited, and when a water-based adhesive or the like is used, it is preferably about 30 to 5000 nm, more preferably about 100 to 1000 nm, and when a UV-curable adhesive, an electron beam-curable adhesive, or the like is used, it is preferably about 0.1 to 100 μm, more preferably about 0.5 to 10 μm.

[0103] The transparent protective film and the polarizing film, or the polarizing film and the functional layer, may be laminated via an intervening layer such as a surface modification layer, an easy-adhesive layer, a blocking layer, or a refractive index adjustment layer.

[0104] Examples of the surface modification treatment for forming the surface modification layer include corona treatment, plasma treatment, primer treatment, and saponification treatment.

[0105] Examples of the adhesive that forms the easy-adhesion layer include forming materials containing various resins having a polyester skeleton, a polyether skeleton, a polycarbonate skeleton, a polyurethane skeleton, a silicone-based skeleton, a polyamide skeleton, a polyimide skeleton, a polyvinyl alcohol skeleton, etc. The easy-adhesion layer is usually provided in advance on a protective film, and the easy-adhesion layer side of the protective film and the polarizing film are laminated with the pressure-sensitive adhesive layer or the adhesive layer.

[0106] The blocking layer is a layer having a function of preventing impurities such as oligomers and ions eluted from a transparent protective film, etc. from migrating (penetrating) into the polarizing film. The blocking layer may be any layer that is transparent and can prevent impurities from eluting from a transparent protective film, etc., and examples of materials for forming the blocking layer include urethane prepolymer-based forming materials, cyanoacrylate-based forming materials, and epoxy-based forming materials.

[0107] The refractive index adjusting layer is a layer provided to suppress a decrease in transmittance caused by reflection between layers having different refractive indices such as the transparent protective film and a polarizing film, etc. Examples of the refractive index adjusting material forming the refractive index adjusting layer include forming agents containing various resins and additives such as silica-based, acrylic-based, acrylic-styrene-based, and melamine-based resins.

[0108] The polarizing film preferably has a polarization degree of 99.98% or more, and more preferably has a polarization degree of 99.99% or more. EXAMPLES

[0109] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.

[0110] <Example 1> <Production of polarizing film> <Production of polarizing film containing water (I-1)> A polyvinyl alcohol film having an average polymerization degree of 2,400, a saponification degree of 99.9 mol%, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was stretched 2.2 times in the conveying direction while swelling by immersing in a swelling bath (water bath) at 20 ° C. between rolls with different peripheral speed ratios (swelling step), and then stretched 3.3 times in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film not stretched at all in the conveying direction) while dyeing by immersing in a dyeing bath (aqueous solution with an iodine concentration of 0.03 wt% and a potassium iodide concentration of 0.3 wt%) at 30 ° C. (dyeing step). Next, the dyed polyvinyl alcohol film was immersed in a crosslinking bath (aqueous solution with a boric acid concentration of 3.0 wt% and a potassium iodide concentration of 3.0 wt%) at 40 ° C. for 28 seconds to stretch 3.6 times in the conveying direction based on the original polyvinyl alcohol film (crosslinking step). Furthermore, the obtained polyvinyl alcohol film was immersed in a 61°C stretching bath (an aqueous solution having a boric acid concentration of 4.0 wt% and a potassium iodide concentration of 5.0 wt%) for 60 seconds to be stretched to 6.0 times in the conveying direction based on the original polyvinyl alcohol film (stretching step), and then immersed in a 20°C washing bath (an aqueous solution having a potassium iodide concentration of 2.0 wt%) for 5 seconds (washing step) to produce a polarizing film containing water.

[0111] <Production of polarizing film impregnated with liquid components (I-2)> Liquid A (a 10 wt % aqueous solution of a compound represented by the following chemical formula (9)) was applied to the water-containing polarizing film obtained above using a wire bar (No. 3, manufactured by Daiichi Rikagaku Co., Ltd.), and the film was left to stand at 25°C for 3 seconds, after which the remaining Liquid A on the surface was wiped off to produce a polarizing film impregnated with the components in the liquid. The moisture content of the water-containing polarizing film, determined by the following measurement method, was 33.0 wt %. [ka]

[0112] [Method for measuring moisture content (weight%) in polarizing film] About 0.2 g of the polarizing film was weighed out and dried at 120° C. for 2 hours. The weight after drying was measured, and the moisture content (W) in the polarizing film was calculated according to the following formula. Moisture content of polarizing film W (weight%) = {(M0-M1) / M0} x 100 M0: Measured weight of polarizing film (g) M1: Weight of polarizing film after drying for 2 hours at 120℃ (g)

[0113] <Production of polarizing film after drying (I-3)> The polarizing film impregnated with the components in the liquid obtained above was dried at 60° C. for 4 minutes to produce a dried polarizing film (hereinafter, simply referred to as a polarizing film). The moisture content of the polarizing film after drying, determined by the above measurement method, was 11.3% by weight. The content of the compound represented by chemical formula (9) in the polarizing film (M H ) is 0.27% by weight, and the content of the compound represented by chemical formula (9) per unit area (m H ) is 5.8μg / cm 2 The thickness (T) of the polarizing film was 18 μm.

[0114] [Method for measuring the content (wt%) of the compound represented by chemical formula (9) in the polarizing film] Approximately 20 mg of the polarizing film was collected, quantified, and dissolved by heating in 1 mL of water, and then diluted with 4.5 mL of methanol. The resulting extract was filtered through a membrane filter, and the concentration of the compound represented by chemical formula (9) was measured using HPLC (Waters ACQUITY UPLC H-class Bio).

[0115] [Content of the compound represented by chemical formula (9) per unit area in the polarizing film (μg / cm 2 ) Measurement method The content of the compound represented by chemical formula (9) per unit area (m H ) was calculated based on the following formula. m H =1.2×T×M H (μg / cm 2 ) T: Thickness of the polarizing film (μm) M H: Content (wt%) of the compound represented by chemical formula (9) in the polarizing film

[0116] <Production of polarizing film> The adhesive used was an aqueous solution containing acetoacetyl-containing polyvinyl alcohol resin (average polymerization degree 1,200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylolmelamine in a weight ratio of 3:1. Using this adhesive, a 40 μm-thick triacetyl cellulose film (moisture permeability 342 g / (m2)) having hard coat layers on both sides of the polarizing film obtained above was coated with the adhesive. 2 After laminating two polarizing films (Konica Minolta, product name "KC4UYW" for 24 hours) using a roll laminator, the film was subsequently heated and dried in an oven (temperature: 60°C, time: 4 minutes) to produce a polarizing film in which transparent protective films were laminated on both sides of the polarizing film.

[0117] [Method of measuring the degree of polarization] The degree of polarization of the polarizing film can be measured using a spectrophotometer (manufactured by JASCO, product name "V7100"). As a specific method for measuring the degree of polarization, the parallel transmittance (H0) and crossed transmittance (H90) of the polarizing film are measured, and the degree of polarization can be calculated from the formula: polarization degree (%) = {(H0-H90) / (H0+H90)}1 / 2×100. The parallel transmittance (H0) is the transmittance value of a parallel laminated polarizing film produced by stacking two identical polarizing films so that their absorption axes are parallel to each other. The crossed transmittance (H90) is the transmittance value of a crossed laminated polarizing film produced by stacking two identical polarizing films so that their absorption axes are perpendicular to each other. These transmittances are Y values ​​corrected for luminosity using a 2-degree visual field (C light source) according to JIS Z 8701-1982.

[0118] [Heat durability rating (A)] The polarizing film obtained above was cut to a size of 5.0 x 4.5 cm so that the absorption axis of the polarizing film was parallel to the long side, and a glass plate (pseudo image display cell) was attached to the protective film surface of the polarizing film on the image display cell side via an acrylic adhesive layer having a thickness of 20 μm, and autoclaved at 50°C and 0.5 MPa for 15 minutes to produce a laminate. The obtained laminate was left to stand in a hot air oven at a temperature of 110°C, and the time until coloration occurred was visually evaluated according to the following criteria. Good: No coloring for more than 500 hours. △: Coloration occurred after 300 hours or more and less than 500 hours. ×: Coloration occurred within 300 hours.

[0119] <Example 2> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 1, except that the polarizing film after the washing step was left to stand at 25° C. for 30 seconds to obtain a polarizing film containing water, and then Liquid A was applied thereto. The results are shown in Table 1.

[0120] <Example 3> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 1, except that the polarizing film after the washing step was left to stand at 25° C. for 1 minute to obtain a polarizing film containing water, and then Liquid A was applied thereto. The results are shown in Table 1.

[0121] <Comparative Example 1> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 1, except that the polarizing film after the washing step was left to stand at 25° C. for 3 minutes to obtain a polarizing film containing water, and then Liquid A was applied thereto. The results are shown in Table 1.

[0122] <Comparative Example 2> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 1, except that the polarizing film after the washing step was dried at 60° C. for 1 minute and then coated with Liquid A. The results are shown in Table 1.

[0123] <Example 4> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing membrane were produced in the same manner as in Example 1, except that a polyvinyl alcohol film having a thickness of 30 μm was used and the iodine concentration in the dye bath was adjusted so that the single transmittance of the finally obtained polarizing membrane was approximately the same, and the above and following measurements were carried out. The results are shown in Table 2. The thickness (T) of the polarizing membrane was 12 μm.

[0124] [Heat durability rating (B)] The polarizing film obtained above was cut to a size of 5.0 x 4.5 cm so that the absorption axis of the polarizing film was parallel to the long side, and a glass plate (pseudo image display cell) was attached to the protective film surface of the polarizing film on the image display cell side via an acrylic adhesive layer having a thickness of 20 μm, and autoclaved at 50°C and 0.5 MPa for 15 minutes to produce a laminate. The obtained laminate was left to stand in a hot air oven at a temperature of 105°C, and the time until coloration occurred was visually evaluated according to the following criteria. Good: No coloring for more than 750 hours. △: Coloration occurred after 750 hours or more and less than 500 hours. ×: Coloration occurred within 500 hours.

[0125] <Comparative Example 3> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 4, except that the polarizing film after the washing step was dried at 60° C. for 1 minute and then coated with Liquid A. The results are shown in Table 2.

[0126] <Example 5> <Production of polarizing film> <Laminate manufacturing (preparation) (II-0)> As the thermoplastic resin substrate, an amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a long shape, a water absorption rate of 0.75%, and a Tg of about 75° C. was used. One side of the resin substrate was subjected to a corona treatment. 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin obtained by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFYMER Z410") at a ratio of 9:1 to prepare a PVA aqueous solution (coating solution). The above PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, and a laminate was manufactured (prepared).

[0127] <Step (II-1) of Producing a Laminate Having a Water-Containing Polarizing Film> The obtained laminate was uniaxially stretched at free end 2.4 times in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130°C (air-assisted stretching process). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by blending 4 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (insolubilizing process). Next, the laminate was immersed in a dyeing bath (an iodine aqueous solution obtained by blending iodine and potassium iodide at a weight ratio of 1:7 with respect to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizing film was approximately the same (dyeing process). Next, the laminate was immersed in a crosslinking bath (a boric acid aqueous solution obtained by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (crosslinking process). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0% by weight) at a liquid temperature of 70° C. and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching process).Then, the laminate was immersed in a cleaning bath (aqueous solution obtained by blending 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. to produce a laminate having a polarizing film containing water (cleaning process).

[0128] <Production of a laminate having a polarizing film impregnated with a liquid component (II-2)> Using a wire bar (No. 3, manufactured by Daiichi Rikagaku Co., Ltd.), Liquid A (a 10 wt % aqueous solution of the compound represented by chemical formula (9)) was applied to the polarizing film surface of the laminate having a polarizing film containing water obtained above, and after leaving it to stand at 25°C for 3 seconds, Liquid A remaining on the surface was wiped off to produce a laminate having a polarizing film impregnated with the components in the liquid. Here, the moisture content of the polarizing film containing water obtained by the above measurement method was 35.5 wt %.

[0129] <Production of polarizing film after drying (II-3)> The film was dried in an oven maintained at 95° C. for 10 minutes (drying process). In this way, a polarizing film having a thickness of 5 μm was formed on the resin substrate. The moisture content of the polarizing film after drying, determined by the above-mentioned measurement method, was 9.9% by weight. The content of the compound represented by chemical formula (9) in the polarizing film (M H ) is 0.41% by weight, and the content of the compound represented by chemical formula (9) per unit area (m H ) is 2.5μg / cm 2 It was.

[0130] <Production of polarizing film> As the adhesive, an aqueous solution containing an acetoacetyl group-containing polyvinyl alcohol resin (average polymerization degree 1,200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylolmelamine in a weight ratio of 3:1 was used. Using this adhesive, a 40 μm-thick triacetyl cellulose film (moisture permeability 342 g / (m)) having a hard coat layer on the opposite side to the resin substrate of the polarizing film obtained above was applied. 2 A polarizing film having a transparent protective film laminated to one side of the polarizing film was produced by laminating a transparent cellulose film (manufactured by Konica Minolta under the product name "KC4UYW") to the polarizing film using a roll laminator and then heating and drying in an oven (at a temperature of 60°C for 4 minutes) to produce a polarizing film having a transparent protective film laminated to one side of the polarizing film. Next, the resin substrate was peeled off, and the above-mentioned triacetyl cellulose film was laminated to the peeled surface using the above-mentioned adhesive by a roll laminator, and then heating and drying in an oven (at a temperature of 60°C for 4 minutes) to produce a polarizing film having a transparent protective film laminated to both sides of the polarizing film.

[0131] [Heat durability rating (C)] The polarizing film obtained above was cut to a size of 5.0 x 4.5 cm so that the absorption axis of the polarizing film was parallel to the long side, and a glass plate (pseudo image display cell) was attached to the protective film surface of the polarizing film on the image display cell side via an acrylic adhesive layer having a thickness of 20 μm, and autoclaved at 50°C and 0.5 MPa for 15 minutes to produce a laminate. The obtained laminate was left to stand in a hot air oven at a temperature of 95°C, and the time until coloration occurred was visually evaluated according to the following criteria. Good: No coloring for more than 750 hours. △: Coloration occurred after 750 hours or more and less than 500 hours. ×: Coloration occurred within 500 hours.

[0132] <Comparative Example 4> <Production of polarizing membranes and polarizing films> A polarizing film and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 5, except that the polarizing film after the washing treatment step was dried at 95° C. for 10 minutes and then coated with Liquid A. The results are shown in Table 3.

[0133] <Example 6> <Production of polarizing membranes and polarizing films> A polarizing membrane and a polarizing film were produced in the same manner as in Example 1, except that in the production of the polarizing membrane, the potassium iodide concentration in the cleaning bath was 4.0% by weight, and liquid B (an aqueous solution containing 10% by weight of zinc sulfate heptahydrate and 0.2% by weight of Olfine EXP.4200 (manufactured by Nissin Chemical Industry Co., Ltd.)) was used instead of liquid A, and the above and following measurements were carried out. The results are shown in Table 4.

[0134] [Measurement of zinc content (wt%) in polarizing film] Approximately 25 mg of polarizing film was weighed into a Teflon container, acid was added, and the container was sealed. The container was then irradiated with microwaves and subjected to pressure acid decomposition at a maximum temperature of 200°C. After complete decomposition, ultrapure water was added to the container to make a constant volume of 50 mL, and the zinc concentration was measured using an ICP-MS (Agilent8800 manufactured by Agilent Technologies). A MARS5 manufactured by CEM was used as the decomposition device.

[0135] [Heat durability rating (D)] The polarizing film obtained above was cut into a size of 5.0 x 4.5 cm so that the absorption axis of the polarizing film was parallel to the long side, and a glass plate (pseudo image display cell) was attached to the protective film surface of the polarizing film on the image display cell side via an acrylic adhesive layer having a thickness of 20 μm, and autoclaved at 50°C and 0.5 MPa for 15 minutes to prepare a laminate. The obtained laminate was left to stand in a hot air oven at a temperature of 105°C for 500 hours, and the test samples were placed in a crossed Nicol position and the cross transmittance (%) at a wavelength of 700 nm was measured using the above spectrophotometer (V7100) and evaluated according to the following criteria. ◯: No red discoloration upon heating (the difference in cross transmittance at a wavelength of 700 nm before and after a heating test at 105°C for 500 hours is less than 1%). ×: Reddening due to heating (the difference in cross transmittance at a wavelength of 700 nm before and after a heating test at 105° C. for 500 hours is 1% or more).

[0136] <Comparative Example 5> <Production of polarizing membranes and polarizing films> A polarizing membrane and a polarizing film were produced and the above measurements were carried out in the same manner as in Example 6, except that the polarizing membrane after the washing step was dried at 60° C. for 1 minute and then coated with Liquid B. The results are shown in Table 4.

[0137] [Table 1]

[0138] [Table 2]

[0139] [Table 3]

[0140] [Table 4]

[0141] The heat durability test described above is affected by the thickness of the polarizing film, so it is sufficient to compare polarizing films having similar thicknesses. It can be seen that the polarizing film of the Example has superior heat durability to the polarizing film of the Comparative Example because it contains a sufficient amount of the components in the liquid.

Claims

1. A method for producing a polarizing film, comprising the steps of: a step (I-1) of producing a water-containing polarizing film by subjecting the polyvinyl alcohol-based film to at least a dyeing step, a crosslinking step, and a stretching step while transporting the polyvinyl alcohol-based film in a longitudinal direction; a step (I-2) of applying a liquid (excluding a treatment liquid having a pH in the range of 3 to 8 and having a buffering effect in said pH range) to the obtained water-containing polarizing film while the water content of the polarizing film is at least 20% by weight, thereby producing a polarizing film impregnated with a component in the liquid; a step (I-3) of subjecting the polarizing film impregnated with the components in the obtained liquid to a drying step to produce a polarizing film after drying having a moisture content of 20% by weight or less; A method for producing a polarizing film, comprising the steps of applying an adhesive to the surface of the resulting polarizing film after drying, on which the liquid has been applied, and laminating a transparent protective film via the adhesive layer.

2. A method for producing a polarizing film, comprising the steps of: A step (II-0) of preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long thermoplastic resin substrate; a step (II-1) of carrying out at least an auxiliary air-stretching step, a dyeing step, and an underwater stretching step on the obtained laminate while conveying the laminate in the longitudinal direction to produce a laminate having a water-containing polarizing film; a step (II-2) of applying a liquid (excluding a treatment liquid having a pH in the range of 3 to 8 and having a buffering effect in said pH range) to the obtained laminate having the water-containing polarizing film while the moisture content of the polarizing film is at least 20% by weight, thereby producing a laminate having a polarizing film impregnated with a component in the liquid; a step (II-3) of subjecting the laminate having the polarizing film impregnated with the components in the liquid to a drying treatment step to produce a polarizing film after drying having a moisture content of 20% by weight or less; A method for producing a polarizing film, comprising the steps of applying an adhesive to the surface of the resulting polarizing film after drying, on which the liquid has been applied, and laminating a transparent protective film via the adhesive layer.

3. 3. The method for producing a polarizing film according to claim 1, wherein the liquid is a solution, and a component in the liquid is a solute.

4. 4. The method for producing a polarizing film according to claim 1, wherein the component in the liquid is a water-soluble compound.

5. 5. The method for producing a polarizing film according to claim 1, wherein the component in the liquid is at least one selected from the group consisting of a radical scavenger, a crosslinking agent, a plasticizer, and a dye.

6. 6. The method for producing a polarizing film according to claim 1, wherein the component in the liquid is a radical scavenger.

Citation Information

Patent Citations

  • Method of alkali saponification of cellulose ester film, surface saponified cellulose ester film and optical film using the same

    JP2004203965A

  • Polarizing plate, optical member provided with the same and liquid crystal display device

    JP2008257025A

  • Method for manufacturing polarizing plate

    JP2013178356A

  • Polarizing plate, liquid crystal display device comprising the same, and method for producing polarizing plate

    JP2015180910A

  • Polarizing plate, liquid crystal display device including the same, and manufacturing method of polarizing plate

    JP2016045434A